Synthesis of biotechnological processes using generalized disjunctive programming - Montagna, Jorge Marcelo (2004)
This article presents a model for the synthesis of a biotechnological process in which a set of biotechnological products must be elaborated. For each of these products, there is a set of hosts that can be used for production. According to the host selected for each product, there is a different set of stages involved in the process. Furthermore, to carry out the task involved at a particular stage, there are different units that can be selected. Depending on the kind of equipment used, different performances can be obtained in terms of the stage yield, dimension required by the unit, processing time, etc. A generalized disjunctive programming model is formulated to solve this problem. This problem is transformed into an MINLP using either a big-M or convex hull reformulation. Both alternatives are solved, and their performances are evaluated.